IMPLEMENTASI GEMAR MENGAJI DALAM PEMBINAAN BACA TULIS AL-QUR’AN PERSPEKTIF PENDIDIKAN ISLAM DI KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - ., Satturi (Universitas Islam Negeri Alauddin Makassar, 2017)
The purpose of this research is: 1) To know the description of the implementation of studying in the District of Marioriwawo Soppeng District, 2) To examine the reading ability of al-Qur'an learners on the implementation of study in the District of Marioriwawo, Soppeng Regency, 3) obstacles and solutions faced in the implementation of learning the Qur'an in fond of Mengaji in District Marioriwawo Soppeng District in an effort to build literacy Qur'an.This research is descriptive qualitative research with approach of study that is normative, pedagogical, and sociological theology. The data source of this research consisted of government, teacher of Koran, and community figure in District of Marioriwawo of Soppeng Regency as informant. Data collection techniques were conducted by conducting interviews of observation and documentation. Processing techniques and qualitative data analysis using 3 stages are 1) data reduction, 2) display data, and 3) conclusion.The result of the research shows that, firstly, the description of the implementation of studying in the District of Marioriwawo, Soppeng Regency is very smooth and the teachers in the District of Marioriwawo, Soppeng District has played an active role in teaching al-Qur'an and developing several methods, and provide effective guidance so that learners can develop optimally in accordance with their potential, and create an environment in the District of Marioriwawo Soppeng religious district. Second, the ability to read al-Qur'an learners on the implementation of fond memories in District Marioriwawo Soppeng District which contains activities that are operational ie; systematic actions and learning, targets to be achieved or desired by government and society, and the activities of the described to instill Qur'anic values to achieve the goals. Third, the constraints and solutions encountered in the implementation of learning the Qur'an in fond of Mengaji in District Marioriwawo Soppeng District in an effort to learn and write al-Qur'an; the first attitude of ignorance of parents to their children in motivating reading and writing al-Qur'an and the influence of technology (HP) is very fast and the participation of parents in the reading and writing of the Qur'an is very minimal. The solution in overcoming the constraints faced namely; parental attitudes in motivation, limited technological influence of HP, intensive guidance, additional tasks of learners, and increased teacher incentives to review and improve training for teachers.The implication of this research is that the educator in Marioriwawo Subdistrict of Soppeng Regency still needs the intensity of reading al-Qur'an and need additional teaching materials of tajwid and makharijul letters, as an insight and provision to develop and applied in the middle of society, it is expected to keep the teacher istiqamah pay attention to reading learners in District Marioriwawo Soppeng district that in fact is good in terms of practice, and need to be improved in terms of material, so that the quality of both in terms of materials and practices can be in line.